2010
DOI: 10.1002/meet.14504701208
|View full text |Cite
|
Sign up to set email alerts
|

Questions are content: A taxonomy of questions in a microblogging environment

Abstract: Microblogging services such as twitter.com have become popular venues for informal information interactions. An important aspect of these interaction is question asking. In this paper we report results from an analysis of a large sample of data from Twitter. Our analysis focused on the characteristics and strategies that people bring to asking questions in microblogs. In particular, based on our analysis, we propose a taxonomy of questions asked in microblogs. We find that microblog authors express questions t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
81
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 71 publications
(86 citation statements)
references
References 25 publications
1
81
0
Order By: Relevance
“…Temporal factors have been shown to provide leverage in several IR-related problems, including document ranking [6] and query difficulty prediction [8].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Temporal factors have been shown to provide leverage in several IR-related problems, including document ranking [6] and query difficulty prediction [8].…”
Section: Related Workmentioning
confidence: 99%
“…Problems such as collaborative and social search [9,11] draw attention to the role that relationships between people play in a variety of search settings. Other work pays specific attention to the social aspects of information seeking in microblog settings [8,16]. More traditional treatments of IR in microblogs is offered in [2,7,10] and [23].…”
Section: Related Workmentioning
confidence: 99%
“…Interrogative tweets detection is closely related to question (subquestion) finding in UGC such as forums, community question answering (CQA) portals and microblogs. There are two divisions for question finding in UGC: rulebased approach [2] and learning-based approach [1,6]. Rulebased approach usually designs several rules from heuristics or observations to check whether a thread or tweet is question or not, while learning-based approach constructs a binary classifier with lexical and/or syntactic features.…”
Section: Related Workmentioning
confidence: 99%
“…and Winget [2] found that 13% of their randomly sampled 2-million tweets corpus were questions. According to the blog of Twitter, on average 1,620 tweets were posted every second in March 2011…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation